Unknown syndrome: microcephaly, facial clefting, and preaxial polydactyly. - Howard, F M (1988)
We present a four year old boy with short stature, disproportionate microcephaly, developmental delay, convulsions, bilateral cleft lip and palate, and bifid right thumb.